POTENSI LOGAM TANAH JARANG DI DALAM ABU BATUBARA: POTENTIAL OF RARE EARTH METALS IN COAL ASH - Purbasari, Diana; Pebrianto, Rosihan; Harsiga, Edwin (Program Studi Teknik Pertambangan Universitas Bangka Belitung, 2023)
Coal is a fossil fuel that is still used as fuel for Steam Power Plants (PLTU). The greater the demand for electrical energy, the greater the need for coal to meet the fuel needs of the PLTU. The combustion of PLTU produces combustion residue in the form of fly ash and solid ash. Fly ash has its own problem level compared to solid ash. The issue of air pollution, sources of disease and radioactive pollutants are the negative impacts of fly ash left over from burning coal. Coal ash is formed from compounds that do not burn in the coal combustion process including the presence of rare earth metals (LTJ). LTJ is a valuable element which in certain levels can be processed into valuable goods. Separation of LTJ in coal can reduce the ash content and improve the quality of coal, so it is necessary to know the potential of LTJ contained in coal ash. The coal sample tested was coal from PT Bukit Asam Tanjung Enim Mining Unit. Identification of LTJ elements in the ash at the PLTU using XRD, ICP and SEM analysis. There is element Cerium (Ce) 55.3 ppm in fly ash and 22.6 ppm in bottom ash, element yttrium (Y) 36 ppm in fly ash and 10.7 ppm in bottom ash, element Lanthanum (La) 27.3 ppm on fly ash and 10.5 ppm on bottom ash. Neodymium (Nd) 26.1 ppm in fly ash and 6.9 ppm in bottom ash. Finally, there is an element of Samarium (Sm) 1.4 ppm in fly ash and 0.7 ppm in bottom ash. There is a promising potential for rare earths in coal ash, but for levels below 500 ppm it is still not feasible to manage, so it is necessary to enrich the rare earths first.